Berber Memories: Women and Jewellery in Morocco, Michel Draguet (2021). Issue 1 (1st March 2022) - Bernabei, Roberta
Review of: Berber Memories: Women and Jewellery in Morocco, Michel Draguet (2021)Brussels: Mercatorfonds and Yale University Press, 600 pp., ISBN 978-0-30025-395-5, h/bk, £65.00s